Comparison of Therapeutic Effects of PVP and PKP Combined With Triple Medication on Mild and Moderate Osteoporotic Vertebral Compression Fracture in the Elderly - Zhou, Yi; Jiang, Jiang; Gu, Fulong; Mi, Daguo (Frontiers in Surgery, 2022)
Objective: To compare and analyze the therapeutic effect of PVP and PKP combined with triple therapy on elderly patients with mild to moderate osteoporotic vertebral compression fractures (OVCF). Methods: 114 cases of elderly patients with mild to moderate osteoporotic vertebral compression fractures in our hospital from January 2017 to January 2018 were identified as research subjects, a total of 136 vertebrae included. The patients who underwent PVP operation were included as the control group with 67 injured vertebrae, and the patients who underwent PKP operation were included as the experimental group with 69 injured vertebrae. Results: the operation time and bone cement injection volume of the experimental group were significantly higher than the control group. The visual analogue scale (VAS) scores of the two groups at 3 months and 6 months after operation were lower than those before operation, with lower VAS scores observed in the experimental group at 3 months and 6 months after operation. The anterior height of the vertebral body in the experimental group was higher than that of the control group. The experimental group outperformed the control group in the incidence of postoperative complications. The postoperative Oswestry dysfunction index (ODI) scores of the two groups were lower before the operation, in which the experimental group had lower scores than the control group (P < 0.05). Conclusion: PVP and PKP combined with postoperative triple therapy can achieve a promising analgesic effect. PKP has a higher volume of bone cement injection volume, and a lower incidence of complications, which gives rise to a better vertebral body recovery height than that of PVP, with rapid postoperative body function recovery and good quality of life.